Inhibitory Effect of Filipendula ulmaria on Mammary Carcinogenesis Induced by Local Administration of Methylnitrosourea to Target Organ in Rats - Bespalov, Vladimir G.; Alexandrov, Valerij A.; Vysochina, Galina I.; Kostikova, Vera A.; Semenov, Alexandr L.; Baranenko, Denis A. (Anti-Cancer Agents in Medicinal Chemistry, 2018)
Background: The meadowsweet (Filipendula ulmaria (L.) Maxim.) may have a cancer prophylactic activity, since its extracts exhibit antioxidant, anti-inflammatory and other effects. We investigated the ability of a meadowsweet decoction to inhibit mammary carcinogenesis induced by intramammary injections of Methylnitrosourea (MNU) to the target organ in rats. Materials and Methods: The chemical composition of meadowsweet extracts was studied by traditional methods. In animal experiments, adult outbred female rats received single injections of MNU at a dose 1mg directly into the tissue of each mammary gland. After carcinogenic exposure one group (MNU) of rats continued to receive standard feed and tap water throughout life. In another group (MNU+meadowsweet), rats were given daily a decoction of the meadowsweet instead of drinking water and standard feed. Results: Meadowsweet extracts showed a sufficiently high content of flavonoids and tannins and also some individual phenolic compounds. In rats after injections of MNU the overall incidence of tumors was 90% with tumor multiplicity of 3.1. The majority of rats (86%) developed multiple malignant tumors of the mammary gland (most often adenocarcinomas). In rats from the group MNU+meadowsweet, there was a statistically significant decrease of the overall tumor multiplicity-by 1.5 times, and the incidence and multiplicity of breast tumors-by 1.6 and 2.2 times, respectively. Conclusions: Meadowsweet extract can be considered an effective inhibitor of breast carcinogenesis.
Keywords: flavonoids